Blastocystis sp., Parasite Associated with Gastrointestinal Disorders: An Overview of its Pathogenesis, Immune Modulation and Therapeutic Strategies - Kumarasamy, Vinoth; Anbazhagan, Deepa; Subramaniyan, Vetriselvan; Vellasamy, Shalini (Current Pharmaceutical Design, 2018)
Blastocystis sp. is a unicellular parasitic microorganism commonly found in the gastrointestinal tracts of humans and animals. It causes symptomatic or asymptomatic infection and its route of transmission is via fecal-oral. High prevalence of Blastocystis infection in developing countries is usually due to poor hygiene practices, exposure to animals infected with the parasite and intake of contaminated water or food. Blastocystis infected individuals often suffer from diarrhea, abdominal pain, nausea, and stomach bloating. Even though pathogenicity of Blastocystis is unclear, it is commonly associated with irritable bowel syndrome. In this review, we have analysed the evidence that shows the association between this microorganism and gastrointestinal disorders. There have been a number of studies which showed that the pathogenicity of Blastocystis is related to its different STs. The pathogenicity is speculated to be due to cysteine proteases formation which stimulates mucosal cells to release interleukin-8 which has been associated with extreme dehydration and gut inflammation. In vitro studies on human colonic epithelial cells revealed that incubation of Blastocystis modulated the host immune response by stimulating the formation of pro-inflammatory cytokines and granulocyte macrophage colonystimulating factor. Metronidazole is found to be the first-line drug of choice. Another treatment option is the combination therapy with trimethoprim/sulfamethoxazole.
Keywords: gastrointestinal tracts